Climatology of the relationship between ozone lamina number and daily/nvalue of total ozone - Križan, P. (Peter) (2016)
This poster deals with relationship between positive and negative lamina number and daily values of total ozone at/nthe ozonosonde stations with sufficient length of observations. We search for this relationship at the European and/nthe Japanese ozonosonde stations as well at the American and Canadian midlatitude stations and at the stations in/nthe high latitudes At the European midlatitude stations there is a strong positive correlations between daily values/nof positive lamina number and daily values of ozone amount up to 30 km. These correlations are weaker and/nnegative for negative lamina number. Are these findings geographically dependent? Is any latitudinal dependence/nof this relationship? Are there any differences between the Arctic and the Antarctica? This poster try to answer/nthese question.